Changes in the use of safe water and water safety measures in water, sanitation and hygiene intervention areas of Bangladesh: a midline assessment - Dey, Nepal C; Ali, ARM Mehrab (BRAC Research and Evaluation Division (RED), 2019)
The BRAC Water, Sanitation and Hygiene (WASH) programme reached 150 upazilas (sub-districts) in collaboration with the Government of Bangladesh since 2006. This study assessed the changes in the use of tubewell water and water safety measures in the households in the 11 upazilas of Bangladesh after BRAC WASH intentions. Data were collected from 6,600 households where 3,812 tubewells were traced in baseline (2006-7) and 3,591 tubewells in midline (2009) . Most of the households (98-99%) used tubewell water for drinking, 70-73% for cooking, 62-66% for washing utensils, 70-73% for cleaning after defecation, and 24 -36% for bathing in midline both in the dry and rainy seasons. The numbers were significantly larger in midline than in baseline (p<0.01) except for drinking in the rainy season. Overall arsenic-free tubewells increased from 58% in baseline to 60% in midline and most households (83%) drank arsenic-free tubewell water in midline. The study revealed that water safety measures including awareness of cleaning/purifying water and hygienic management of water increased significantly (p<0.01 ). The concrete-built platform increased from 63% in baline to 69% in midline. Tubewell platforms were cleaned (32%) in baseline, which increased to 46% in midline. However, there still remained impediments to 100% safe water use by the households include arsenic contamination of tubewell water, financial inabilities of the ultra poor and poor households for installing tubewells for arsenic-free water. unmarked tubewell (whether contaminated by arsenic or not). The study concluded that WASH inteNention has succeeded in increasing access to safe water use. hygienic management of water, and cleanliness of water collecting point in the study areas. It is encouraging to note that ultra poor households had interest to get new tubewells and preferred to pay the costs in monthly installments, which indicates that these households were aware of the benefits of safe water. Thus, BRAC WASH programme needs to pay further attention to these impediments at the household level in order to further improve the current situation.